Comparison of natural flower dye extraction from fresh and dried blue pea flower using methanol in dye sensitized solar cell application / Muhammad Hasrul Akashah Azrangi @ Azra’al - Azrangi @ Azra’al, Muhammad Hasrul Akashah (2024)
In this report, the dye of blue pea flower, dried and fresh form, are extracted using methanol as the solvent. The dye is then undergoing doping methods using CaO. The purpose of this research is to fine the best conductivity delivers from the dye whether it is fresh or dried form and then determine whether it can be absorbed by the dopant specifically CaO in doping. The highest conductivity of the dye is the 3 days of the dried blue pea flowers extraction in which the conductivity value is 2000(^S/cm).